Poor Students, Rich Teaching : Seven High-Impact Mindsets for Students from Poverty (Using Mindsets in the Classroom to Overcome Student Poverty and Adversity). - Jensen, Eric (Solution Tree, 2019)
This book examines how poverty affects education, achievement, and motivation for students across the U.S. and explores seven mindsets for ensuring college and career readiness for all students, regardless of socioeconomic status.